The Current Discussion on Austrian Family Benefits – Indicating a Major Dissensus on the Interpretation of EU Law - Alexander Balthasar (Central European Public Administration Review)
In early 2018, Austria amended its family benefits law by introducing ‘indexation’ according to the average living costs of the country where the child actually resides. What seems to be, at first sight, a flagrant breach of EU law (in particular of Article 7 of Regulation [EC] 883/2004) is, when looking deeper, much more complicated and might very well be only a symptom of deeply rooted differences in the interpretation of current, post-Lisbon Union law,